Exposure to benzene, toluene and polycyclic aromatic hydrocarbons in Nunavimmiut aged 16 years and over (Nunavik, Canada) : Qanuilirpitaa 2017 survey - Caron-Beaudoin, Élyse; Ayotte, Pierre; Aker, Amira; Blanchette, Caty; Ricard, Sylvie; Gilbert, Véronique; Avard, Ellen; Lemire, Mélanie (Environmental Research, 2022)
There are numerous volatile organic compounds (VOCs) and polycyclic aromatic hydrocarbons (PAHs) that Inuit may be exposed to from combustion, cooking, heating, vehicle exhaust, active and passive smoking and other local sources of contaminants such as oil spills or open-air burning in landfills. To better assess the levels of exposure to these non-persistent chemicals, we measured a suite of benzene, toluene (two VOCs) and PAHs metabolites in pooled urine samples from youth and adults aged 16 years old and over who participated in the Qanuilirpitaa? 2017 Inuit Health Survey (Q2017), a population health survey conducted in Nunavik. A cost- effective pooling strategy was established and 30 different pools from individual urine samples (n =1266) were created by grouping individual urine samples by sex, age groups and regions. To assess smoking and exposure to second-hand smoke, cotinine levels were measured in individual urine samples. We found that benzene, toluene, all detected PAHs metabolites and cotinine levels were significantly higher in Q2017 compared to adults in the Canadian Health Measure Survey Cycle 4 (2014–2015) or the general U.S population (2015–2016). Moreover, mean levels of one benzene metabolite, S-phenylmercapturic acid, and several PAHs metabolites, 1-naphthol, 2-and 3-hydroxyfluorene, and 4- and 9-hydroxyphenanthrene, known to be associated with smoking habits, were higher in Q2017 compared to reference values (RV95) established for non-smokers in the general Canadian population. Furthermore, benzene and PAHs metabolites were all correlated with cotinine levels. Our results suggest that the high smoking prevalence in Nunavik is an important contributor to the elevated benzene and PAHs exposure. Other local sources may add to that exposure, although we were not able to account for their contribution. These data highlight the importance of regional and community efforts for reducing smoking and to encourage smoke-free homes in Nunavik, while continuing to investigate and reduce other possible ...